ETHNOMEDICINE AS CULTURAL HERITAGE : SUSTAINABLE TOURISM POTENTIAL IN SEBELAT VILLAGE - Jannah, Wita Izzatul; Dienaputra, Reiza D.; Khadijah, Ute Lies Siti (Sosiohumaniora, 2026)
This study examines the potential of ethnomedicine as cultural heritage and its contribution to sustainable tourism development in Sebelat Village, Midai Island. Using a qualitative descriptive approach, the study involved eight participants consisting of traditional healers, patients, community members, and local stakeholders selected through purposive sampling. Data were collected through in-depth interviews, observations, documentation, and literature review, and analyzed descriptively using SWOT analysis supported by IFAS and EFAS matrices. The findings reveal that the Midai community continues to practice various forms of ethnomedicine, including betetas, betangas, traditional massage, luluran, bekasai, param, bajong, kecundoi, jamu, sekapur sirih, and aek tawa, reflecting local knowledge related to health, spirituality, and the relationship between humans and the environment. These practices possess cultural, symbolic, and experiential values that support their potential development as cultural, educational, and wellness tourism attractions. The recommended development strategies include strengthening community participation, establishing healer communities, developing ethnomedicine-based tourism packages, and integrating cultural values into village tourism planning. This study concludes that ethnomedicine represents an important cultural resource that may support sustainable tourism development while contributing to cultural preservation and local economic diversification. Future research is recommended to adopt broader interdisciplinary approaches to further examine ethnomedicine within tourism and cultural heritage contexts.